Carnivoran hunting style and phylogeny reflected in bony labyrinth morphometry - Schwab, Julia A. (Sci Rep, 2019)
Carnivorans are a highly diverse and successful group of mammals, found on the top of the food chain. They originated in the Palaeocene (ca. 60 Ma) and have developed numerous lifestyles, locomotion modes and hunting strategies during their evolutionary history. Mechanosensory organs, such as the inner ear (which houses senses of equilibrium and hearing), represent informative anatomical systems to obtain insights into function, ecology and phylogeny of extant and extinct vertebrates. Using µCT scans, we examined bony labyrinths of a broad sample of various carnivoran species, to obtain new information about hunting behaviours of ancient carnivorans. Bony labyrinths were digitally reconstructed and measurements were taken directly from these 3D models. Principal component analyses generally separated various hunting strategies (pursuit, pounce, ambush and occasional), but also support their phylogenetic relationships (Canoidea vs. Feloidea). The height, width and length of all three semicircular canals show functional morphological adaptations, whereas the diameter of the canals, the height of the cochlea and particularly the angle between the lateral semicircular canal and the cochlea indicate a phylogenetic signal. The results demonstrate that the bony labyrinth provides a powerful ecological proxy reflecting both predatory habits as well as phylogenetic relationships in extinct and extant carnivorans.